Measurement of Level Density Using spectral distribution Method and Comparison with Bethe Formula - Gharghar, Fawzeya (Aljameai, 2022)
Abstract: Nuclear level densities of some heavy nuclei have been calculated taking into consideration the effect of one-body interaction. We use the Hamiltonian moments method based upon the statistical calculation using the Nilsson Hamiltonian for the single particle energies. The density is then constructed in terms of the moments of the Hamiltonian which are defined using spectral distribution methods. The results indicated that the Gaussian function is appropriate to describe the nuclear level density. The present calculated results have been compared with the standard Bethe formula and good agreement was obtained. Bethe parameter has been determined during the fit. الملخص: في هده العمل تناولنا بالدراسة الكثافة النووية لمستويات طاقة الأنوية وقمنا بأستخدام القوانين الخاصة بنظرية التوزيع الطيفي مع الأخد بعين الاعتبار أن الجسيمات داخل النواة (البروتونات والنيوترونات) غير متفاعلة مع بعضها البعض. تم المقارنة بين النتائج المتحصل عليها لعدد من الأنوية الثقيلة وبين صيغة بيثيه بأعتبارها المعادلة المتفق عليها لحساب كثافة المستويات النووية وتوصلنا الي نتائج جيدة خلال هده المقارنة.